AIDS patient with severe T cell depletion achieved control but not clearance of SARS‐CoV‐2 infection. Issue 2 (4th December 2021) - Spinicci, Michele; Mazzoni, Alessio; Borchi, Beatrice; Graziani, Lucia; Mazzetti, Marcello; Bartalesi, Filippo; Botta, Annarita; Tilli, Marta; Pieralli, Filippo; Coppi, Marco; Giovacchini, Nicla; Colao, Maria Grazia; et al.
Abstract : A late presenter AIDS patient with severe T cell depletion presented non‐severe COVID‐19 symptoms, with prolonged viral shedding. Our case report supports the hypothesis that an effective T cell response may be dispensable for the control of COVID‐19 progression to severe forms, while it may be necessary for SARS‐CoV‐2 clearance.